2009
DOI: 10.1073/pnas.0812149106
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the global cellular thiol–disulfide status

Abstract: It is widely accepted that the redox status of protein thiols is of central importance to protein structure and folding and that glutathione is an important low-molecular-mass redox regulator. However, the total cellular pools of thiols and disulfides and their relative abundance have never been determined. In this study, we have assembled a global picture of the cellular thiol-disulfide status in cultured mammalian cells. We have quantified the absolute levels of protein thiols, protein disulfides, and glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
311
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(340 citation statements)
references
References 38 publications
23
311
2
4
Order By: Relevance
“…Given that the uptake of cystine through system Xc-is a rate-limiting step in glial synthesis of GSH (Griffith, 1999;O'Connor et al, 1995) and the importance of GSH in maintaining cellular redox potential (Lopez-Mirabal and Winther, 2008), it was surprising that withdrawal from daily cocaine did not alter accumbens redox potential (considered the most general index of oxidative stress (Jones et al, 2000)). However, it has been suggested that changes in cellular protein thiol status could be a more accurate indicator of redox status, because protein thiols represent a larger potential redox pool than free GSH (Hansen et al, 2009). Importantly, withdrawal from daily cocaine reduced the level of free sulfhydryls, consistent with an increase in protein S-glutathionylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the uptake of cystine through system Xc-is a rate-limiting step in glial synthesis of GSH (Griffith, 1999;O'Connor et al, 1995) and the importance of GSH in maintaining cellular redox potential (Lopez-Mirabal and Winther, 2008), it was surprising that withdrawal from daily cocaine did not alter accumbens redox potential (considered the most general index of oxidative stress (Jones et al, 2000)). However, it has been suggested that changes in cellular protein thiol status could be a more accurate indicator of redox status, because protein thiols represent a larger potential redox pool than free GSH (Hansen et al, 2009). Importantly, withdrawal from daily cocaine reduced the level of free sulfhydryls, consistent with an increase in protein S-glutathionylation.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of xCT reduces extracellular glutamatergic tone on synaptic mGluRs and this is thought to contribute to the vulnerability to reinstate cocaineseeking (Kalivas, 2009). Moreover, system Xc-is rate limiting in supplying cystine substrate for GSH synthesis Xc- (McBean, 2002) and the increase in glutationylated protein may serve as a reserve source of GSH (Hansen et al, 2009); making it possible that the cocaine-induced regulation of GSTP1P2 might be related to the reduction in system Xc-. While an interaction may still be possible, deletion of GSTP1P2 did not regulate xCT levels; although the constitutive nature of the genetic deletion leaves open the possibility that developmental compensation may have masked an interaction between system Xc-and GSTP1P2.…”
Section: System Xc-and Cocaine-induced Changes In Redoxmentioning
confidence: 99%
“…Sequential reduction and alkylation of gliotoxin, followed by detection using RP-HPLC, MALDI-ToF MS, or TLC represents a new direction for the improved detection of gliotoxin, whereby the molar absorption of the labelled form is almost sevenfold greater than free gliotoxin. This observation of enhanced sensitivity has not been forthcoming from elegant investigations of glutathione detection following modification with N-(1-pyrenyl)maleimide and subsequent HPLC identification of the resultant product [26]. Although GT-(AF) 2 was fluorescent, it was observed that fluorescence quenching, under the acidic conditions employed for RP-HPLC identification, was apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The thiol moiety in cysteine residues is susceptible to a variety of oxidative post-translational modifications driven by the capacity of sulfur to adopt several stable oxidation states [5]. Protein thiols potentially make a substantial contribution to the redox buffering of the cell through reversible oxidation at cysteine residues, the most familiar example of which involves disulfide bond formation [6]. In addition to disulfide bond formation, reaction of cysteine thiolates with hydrogen peroxide, the major ROS in the cell [7], produces cysteine sulfenic acid residues (RSOH).…”
Section: Introductionmentioning
confidence: 99%